2022
DOI: 10.1108/ijhg-03-2022-0027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of health expenditure on average life expectancy: does government effectiveness play a moderating role?

Abstract: PurposeThis study investigates the impact of total health expenditure on life expectancy in a panel of 43 African countries from 2000 to 2018.Design/methodology/approachThe dynamic panel generalized method of moments (GMM) estimation method developed by Arellano and Bond (1991) is used in this study. This approach generates estimates that are heteroskedasticity and autocorrelation consistent, as well as controls for unobserved time-invariant country-specific effects and eliminates any endogeneity in the panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
0
13
0
3
Order By: Relevance
“…iii) The results provided by the literature reveal that economic growth improves health status (Sirag et al, 2017;Majeed et al, 2021;Bouchoucha, 2021;Wang et al, 2020a;Azam et al, 2022;Bunyaminu et al, 2022;Hendrawaty et al, 2022;Sial et al, 2022). On the other hand, Ecevit et al (2022) indicate that economic growth negatively affects health outcomes in Turkey.…”
Section: Literaturementioning
confidence: 98%
“…iii) The results provided by the literature reveal that economic growth improves health status (Sirag et al, 2017;Majeed et al, 2021;Bouchoucha, 2021;Wang et al, 2020a;Azam et al, 2022;Bunyaminu et al, 2022;Hendrawaty et al, 2022;Sial et al, 2022). On the other hand, Ecevit et al (2022) indicate that economic growth negatively affects health outcomes in Turkey.…”
Section: Literaturementioning
confidence: 98%
“…GE plays an essential role in promoting green economy even in developed and in developing countries [19]. GE has a moderating effect in the positive relationship between health individual expenditures and life expectations [20]. Even if GE is related to jurisdiction, the size of jurisdiction has no impact on GE [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While De Micco et al (2022) do not write explicitly about the COVID-19 pandemic, their article is highly applicable as they present a review of the literature on the costs of introducing a new vaccine in Sub-Saharan Africa. Bunyaminu et al (2022) ask whether per capita health expenditure is the only factor responsible for differences in life expectancy or whether this is mitigated by the effect of good governance. Lytvyn et al (2022) write about innovations in healthcare regulations in the Ukraine, but oddly, for an article submitted in 2022, say nothing about the impact of war on the provision of healthcare in that nation.…”
Section: Introductionmentioning
confidence: 99%
“…However, challenges to population health may be experienced more acutely in developing nations with multiple urgent demands on public finance. Bunyaminu et al (2022) conducted a study examining health data from 43 African nations covering a period of 18 years from 2000 to 2018. The literature review supporting this work indicated that greater health expenditure increases life expectancy; however, this finding was challenged when the level of general economic development was factored into the equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation